Flattening the COVID-19 curve: Emotions mediate the effects of a persuasive message on preventive action - Muis, Krista Renee; Sinatra, Gale M.; Pekrun, Reinhard; Kendeou, Panayiota; Mason, Lucia; Jacobson, Neil G.; Van Tilburg, Wijnand Adriaan Pieter; Orcutt, Ellen; Zaccoletti, Sonia; Losenno, Kelsey M. (Frontiers in Psychology, 2022)
Introduction Across four countries (Canada, USA, UK, and Italy), we explored the effects of persuasive messages on intended and actual preventive actions related to COVID-19, and the role of emotions as a potential mechanism for explaining these effects. Methods One thousand seventy-eight participants first reported their level of concern and emotions about COVID-19 and then received a positive persuasive text, negative persuasive text, or no text. After reading, participants reported their emotions about the pandemic and their willingness to take preventive action. One week following, the same participants reported the frequency with which they engaged in preventive action and behaviors that increased the risk of contracting COVID-19. Results Results revealed that the positive persuasive text significantly increased individuals’ willingness to and actual engagement in preventive action and reduced risky behaviors 1 week following the intervention compared to the control condition. Moreover, significant differences were found between the positive persuasive text condition and negative persuasive text condition whereby individuals who read the positive text were more willing and actually engaged in more preventive action compared to those who read the negative text. No differences were found, however, at the 1-week follow-up for social distancing and isolation behaviors. Results also revealed that specific discrete emotions mediated relations between the effects of the texts and preventive action (both willing and actual). Discussion This research highlights the power of educational interventions to prompt behavioral change and has implications for pandemic-related interventions, government policy on health promotion messages, and future research.